Pemberian Materi Tentang Keseruan Bermatematika dan Pentingnya Ilmu Matematika Kepada Siswa/i SMP Negeri Wakapsir - Landerius Maro (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Mathematics is a subject that is considered difficult and frightening for almost all students, so that their interest in learning decreases and impacts their academic achievement in that subject. This encourages the importance of this community service activity to foster students' love for mathematics and open their horizons about the importance of mathematics in everyday life. Mathematical games can make students enthusiastic about taking mathematics lessons, while the implementation of mathematics in everyday life can open up insight for them about the importance of mathematics. The target of this activity is class VIII students of SMP Negeri Wakapsir. This activity went well without any problems due to the good reception from the Head, Staff, and Teachers of SMP Negeri Wakapsir, especially the mathematics teacher, and was complemented by the enthusiasm of the students who participated in this activity in listening, listening, and being actively involved in participating this activity. The results obtained from this activity were in the form of differences in students' views regarding mathematics between before and after the activity, where views that were initially negative became positive after going through this service activity.